2022
DOI: 10.1609/icwsm.v16i1.19393
|View full text |Cite
|
Sign up to set email alerts
|

On the Context-Free Ambiguity of Emoji

Abstract: Due to their pictographic nature, emojis come with baked-in, grounded semantics. Although this makes emojis promising candidates for new forms of more accessible communication, it is still unknown to what degree humans agree on the inherent meaning of emojis when encountering them outside of concrete textual contexts. To bridge this gap, we collected a crowdsourced dataset (made publicly available) of one-word descriptions for 1,289 emojis presented to participants with no surrounding text. The emojis and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…While KevinMcKenzie claims that he was the first who proposed the smiley in an email on April 12, 1979 (Raymond, 1996). For Crystal (2001), emoticons are combinations of keyboard characters invented to show an emotional facial expression. Nearly all of the emoticons are read sideways.…”
Section: From Emoticon To Emojimentioning
confidence: 99%
See 1 more Smart Citation
“…While KevinMcKenzie claims that he was the first who proposed the smiley in an email on April 12, 1979 (Raymond, 1996). For Crystal (2001), emoticons are combinations of keyboard characters invented to show an emotional facial expression. Nearly all of the emoticons are read sideways.…”
Section: From Emoticon To Emojimentioning
confidence: 99%
“…Therefore, they created a new dataset called EmoSim508, which assigns human annotated semantic similarity scores to a set of 508 carefully selected emoji pairs. Częstochowska et al (2022) found out that emojis come with very different amounts of prepacked semantics. A number of emojis are completely unambiguous, whereas the majority of annotators describe them with the same word.…”
Section: Ambiguity Of Polysemous Emojismentioning
confidence: 99%
“…without much potential for ambiguity nor room for interpretation. Cz ęstochowska et al (2022) analyzed ambiguity rates for different categories of emoji based on participant descriptions of individual emoji presented without surrounding context. They found "food & drink," "clothes & accessories," "nature," and "hearts" to be the categories with the least variation.…”
Section: Emoji Meaningsmentioning
confidence: 99%
“…We first turn to our analysis of offline emoji lexicalization: do people agree on the meanings of emoji? Intuitively and evidently (Częstochowska et al., 2022), some emoji should have high meaning agreement (e.g., many of the animals, foods, and objects). Others, however, are not as straightforward—some are polysemous with multiple widely recognized meanings, like the notoriously euphemistic peach and eggplant, and others may not have any clearly accepted and widely agreed upon meaning.…”
Section: Experiments 1: Emoji Meaning Agreementmentioning
confidence: 99%
See 1 more Smart Citation